2005
DOI: 10.1039/b408129n
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent crystal structure of ferroelectric Ba2LaTi2Nb3O15

Abstract: The crystal structure of Ba 2 LaTi 2 Nb 3 O 15 was determined using high resolution powder neutron diffraction data collected at 100 K and 400 K. Both structures, refined in space groups P4bm (100 K) and P4/mbm (400 K), are closely related tetragonal tungsten bronzes with Ba in large 15-coordinate sites, La in 12-coordinate sites and Nb,Ti disordered over octahedral sites. The structural origin of the low temperature ferroelectricity is attributed primarily, from variation in bond lengths with temperature, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 8 publications
4
45
0
Order By: Relevance
“…5. 5,6 Additional rows of weak spots are seen, consistent with a doubling of the c axis. However, the superlattice is also present in the [1 1 0] direction, but its periodicity is incommensurate with that of the sublattice.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…5. 5,6 Additional rows of weak spots are seen, consistent with a doubling of the c axis. However, the superlattice is also present in the [1 1 0] direction, but its periodicity is incommensurate with that of the sublattice.…”
Section: Introductionmentioning
confidence: 54%
“…However, the superlattice is also present in the [1 1 0] direction, but its periodicity is incommensurate with that of the sublattice. 5 More recent studies on other M analogues 6 show that all possess a superlattice with a doubling of c; however, the periodicity parallel to [1 1 0] is incommensurate for M = La, Bi but commensurate for smaller rare earths, e.g. Nd, Sm, Gd.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…But for the Ba 4 Ln 2 Ti 4 M 6 O 30 compounds, not all the ordered tungsten bronze structure compounds tend to be normal ferroelectric nature, such as Ba 4 La 2 Ti 4 Nb 6 O 30 [15,16]. Stennett et al [17] suggested that the lack of commensurate periodicity may contribute to the disruption of long range dipolar coupling in these compositions, resulting in relaxor rather than classic ferroelectric behavior, which leading by the effects of the ionic radius of rare-earth ion in interstice A1.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, the incommensurate structure of SBN was solved and refined as a five dimensional (5D) modulated structure in the superspace formalism. [49] In 2012, Graetsch et al [50][51] [52][53][54][55] demonstrated that both Bi-and La-based compounds exhibit relaxor behavior, whereas Nd-, Sm-, and Gd-based analogs are classical ferroelectrics. In Ba 2 RENb 3 Ti 2 O 15 compounds, deviations from the ideal TTB symmetry caused by an incommensurate modulation was associated with relaxor behavior, whereas a commensurate modulation was observed for phases exhibiting ferroelectric behavior.…”
Section: Wwweurjicorg Full Papermentioning
confidence: 99%